Accessing healthcare as a person with a rugby-related spinal cord injury in South Africa: the injured player's perspective. (2nd November 2022) - Badenhorst, Marelise; Verhagen, Evert; Lambert, Mike; van Mechelen, Willem; Brown, James
ABSTRACT: Background: Rugby carries a risk for serious injuries, including acute spinal cord injuries. The lifetime health consequences of these injuries may be far-reaching. Purpose: In this study, we aimed to describe barriers and facilitators to healthcare and rehabilitation, in individuals with rugby-related spinal cord injuries in South Africa. Methods: This study adopted a pragmatic qualitative approach. Stratified purposive sampling was used to select interviews from players from a variety of socio-economic status and geographical areas for inclusion in this study. The final sample consisted of thirty-one (n = 31) participants. Thematic analysis was used to analyze the data. Results: Participants described long-term, accessible, affordable, quality healthcare and rehabilitation as important contributors to their quality of life. Even though public healthcare is accessible from a cost point of view, quality of care, availability of rehabilitation services and factors such as affordability and availability of adequate transport remain a barrier for lower socio-economic groups. Conclusion: This population was unique, as the support from a dedicated organization enabled participants to overcome some barriers, highlighting the challenges of the healthcare system in maintaining the health of people with spinal cord injuries. Every effort should be made to create equitable access to healthcare and rehabilitation for persons with spinal cord injuries in South Africa.